MENINGKATKAN KEMAMPUAN METAKOGNISI DAN HASIL BELAJAR BIOLOGI SISWA SMA PGRI 1 PUNGGUR MELALUI PENERAPAN METODE INKUIRI TERBIMBING (GUIDE INQUIRY) - Hadizah, Elys; Muhfahroyin, Muhfahroyin (Bioedukasi Jurnal Pendidikan Biologi, 2012)
in general, method of inquiry guide can increasing the capability of metakognitive and result of students. metacognition is thinking about thinking. Metacognition goes beyond thinking (meta+cognition) in that it is the active awareness and knowledge of oneâs own thinking processes. Metacognitive skill are sometimes refered to as âself direction skills. Metacognitive could be different between the high and low student. This result showe in research to class ten of three grade student of senior high school in PGRI Punggur. The result showed so that using inquiry guide-metacognitive to the aspect of self-planning with activity formulate problem and formulate guess while with score applying 66,78, aspect self-monitoring with activity collect information and testing guess while with score applying 61,10, and aspect self evaluating with activity conclude and summary with score applying 71,37.Â Kata kunci: Guide Inquiry, kemampuan Metakognisi, Hasil Belajar